O papel discursivo do especialista: em debate, o trânsito nos minipúblicos e nos media - Marcela Dantas Laranjeira (2011)
This work aims both to analyze the specialist discursive role in different debateenvironments concerned about urban transit and transportation systems discussions. Weare interested in apprehending deliberative differences found on the utterances of thiskind of actor as a way of opportunities perceptions and eventual constraints caused bythe environments chosen by us: the minipublics and media. For this, it was necessary toreduce our field research in a sub-theme. In this way, we have done the option ofworking with the Law Project n° 1.508/07 which provided the Belo Horizonte busterminal transfer, located on the Center area of the city, to the Calafate region.Therefore, it was necessary to survey, in a preliminary moment, the history of the transiton the capital and drawing a general comprehension about the subject. Subsequently wepresent the technical community linked to the traffic subject and the concept ofspecialist, the main actor focused on this research. To present our comprehension aboutthe issue of expertise, it was necessary to make a theoretical resumption, which one hadto present the origin of experts, resulted from the labor division process and the mainfeatures pointed out by scholars in this field. We saw the specialist actor, then, as anassistant to the social process and a tyrant technocrat, but decided that his role ismultiple and we should not frame him in a unique way. After contextualizing the mainactor of our process, it was the moment to focus on the process exactly. From ahabermasian perspective, we treated before of deliberation process and later of theresearch environments, the media, the place for the visibility to excellence, and theminipublics, closest kind of environment to achieve high-level deliberation. After thetheoretical treatment, we choose our research methodology and present our workinghypotheses. Contributed in Steiner et al (2004) we have exposed and discussed the DQI(Discourse Quality Index), methodology developed by these authors. On the results ofour analysis we observed the existence of an intertwining between the media andminipublics environments, where the second one allured the visibility of the first and, inthis way, the actors become to behave similarly in both situations. Another importantfinding was the relationship between opportunities and constraints present in both typesof environments. Generally we could realize that there are no opportunities andconstraints acting as absolute truths on the two analyzed kind of environment.